Differential Apoptotic Responses of Hemocyte Subpopulations to White Spot Syndrome Virus Infection in Fenneropenaeus chinensis - Cui, Chuang; Liang, Qianrong; Tang, Xiaoqian; Xing, Jing; Sheng, Xiuzhen; Zhan, Wenbin (Frontiers in Immunology, 2020)
The apoptosis of hemocytes plays an essential role in shrimp immune defense against viral infections. In order to further elucidate the differential apoptotic responses of the granulocytes and the hyalinocytes in Fenneropenaeus chinensis post WSSV infection, the characteristics of apoptosis and the viral proliferation in total hemocytes and hemocyte subpopulations were respectively investigated in the present work. The results showed that at different stages of WSSV infection, the apoptotic rate of hemocytes changed significantly, and the apoptosis-related genes also showed significantly differential expression responses. Interestingly, we found that in the early stage of WSSV infection, the apoptotic rate of virus-negative hemocytes was significantly higher than that of virus-positive hemocytes, while it was significantly lower than that of virus-positive cells in the middle and late infection stages. The apoptotic difference between virus-positive and virus-negative hemocytes seems to be an important way for the WSSV to destroy the host's immune system and facilitate the virus spread at different infection stages. It was further found that the apoptosis rate of granulocytes was always significantly higher than that of hyalinocytes during WSSV infection, indicating that granulocytes have a stronger apoptotic response to WSSV infection. Moreover, a higher viral load was detected in granulocytes, and the density of granulocytes decreased more rapidly post WSSV infection, indicating that the granulocytes are more susceptible and vulnerable to WSSV infection compared with the hyalinocytes. These results collectively demonstrated that the apoptotic response of shrimp hemocytes could be significantly influenced by the WSSV infection, and the differential apoptotic response of granulocytes and hyalinocytes to WSSV indicated the differences of antiviral mechanisms between the two hemocyte subpopulations.